Efektivitas Sibumil (Aplikasi Deteksi Risiko Kehamilan Mandiri) Berbasis Android Di Kota Pekalongan Tahun 2021 - Suparni Suparni; Aslam Fatkhudin; Nina Zuhana (JURNAL LITBANG KOTA PEKALONGAN, 2021)
The Covid-19 pandemic has caused restrictions on many activities, including pregnancy checks, because feared that pregnant women will contract the virus. So we need an innovation for pregnant women to know the risk of pregnancy to get the right treatment. This study aims to determine the effectiveness of the SiBumil application, which is an application to detect the risk of independent pregnancy. The population in this study were pregnant women with high risk in the Kramatsari Public Health Center, Pekalongan City as many as 103 as samples using the Krejcie and Morgan tables based on an error of 5%. Primary data collection methods are carried out by direct assistance to pregnant women and distributing questionnaires. The results of the analysis using the alpha test with the Black box technique showed that the functions of all the menus in SiBumil were successfully executed. For the feasibility test using the usability test, an average of 84% was obtained, indicating that this application is very feasible to use. For differences in knowledge using the Wilcoxon test, p value was obtained 0.000 < ? (0.05) so it was concluded that there was a difference in knowledge before and after the use of SiBumil.  Keywords: SiBumil, pregnant women, android based, pregnancy risk detection